2005
DOI: 10.1213/01.ane.0000181338.35454.6a
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Intravenous Ondansetron and Dolasetron in Intrathecal Morphine-Induced Pruritus: A Randomized, Double-Blinded, Placebo-Controlled Study

Abstract: Pruritus is the most common side effect of intrathecal morphine for postoperative pain relief. Activation of central 5-hydroxytryptamine subtype 3 (5-HT3) receptors is one of its possible mechanisms. The role of 5-HT3 antagonists in the prevention of pruritus has not been clearly established. In a prospective, randomized, double-blind, placebo-controlled study, we evaluated the efficacy of prophylactic administration of ondansetron and dolasetron for the prevention of intrathecal morphine-induced pruritus. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
1
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 16 publications
1
40
1
1
Order By: Relevance
“…Moreover, nalbuphine was shown to be ineffective in the treatment of postoperative opioid-induced pruritus in paediatric patients (149), The usage of 5-HT3 receptor antagonists (ondansetron, dolasetron) remains controversial. Some authors reported good efficacy (123,141,(150)(151)(152) while others denied it (153)(154)(155). In addition, antihistaminics, droperidol, propofol, alizapride, tenoxicam and diclofenac have been tried with various success (116,124,141,156).…”
Section: Opioid-induced Pruritusmentioning
confidence: 99%
“…Moreover, nalbuphine was shown to be ineffective in the treatment of postoperative opioid-induced pruritus in paediatric patients (149), The usage of 5-HT3 receptor antagonists (ondansetron, dolasetron) remains controversial. Some authors reported good efficacy (123,141,(150)(151)(152) while others denied it (153)(154)(155). In addition, antihistaminics, droperidol, propofol, alizapride, tenoxicam and diclofenac have been tried with various success (116,124,141,156).…”
Section: Opioid-induced Pruritusmentioning
confidence: 99%
“…One of the possible mechanisms of pruritus is related to direct stimulation of 5-HT3 receptors by morphine in the dorsal horn of the spinal cord and medulla, therefore 5-HT3 antagonists may be beneficial in its treatment. 10 Previous studies by Yeh et al 4 and Charuluxananan et al 5 demonstrated that prophylactic ondansetron reduced the frequency of pruritus in patients undergoing caesarean section. Conversely, three recent studies 6,7,9 comparing longer acting 5-HT3 antagonists reported the failure of ondansetron, tropisetron and granisetron to prevent pruritus after caesarean section.…”
Section: Discussionmentioning
confidence: 97%
“…Los medicamentos específicos son: dolasetrón (reduce el vómito) [23][24][25][26][27] , granisetrón (reduce el vómito) 28-32 y ondansetrón (reduce el vómito y rescates antieméticos) [28][29][30][33][34][35][36][37][38][39][40][41][42][43][44][45] .…”
Section: Antieméticos 5ht3unclassified